Production and characterization of polyhydroxybutyrate (PHB) produced by Bacillus sp. isolated from Egypt - Mohamed A. Hassan, Elsayed K. Bakhiet, Salah G. Ali, Hussien R. Hussien (Journal of Applied Pharmaceutical Science, 2016)
Synthetic polymers are non-degradable and accumulated in the environment so, the efforts of scientists were forwarded to provide us with alternative environmentally biopolymers. Polyhydroxyalkanoates (PHAs) including polyhydroxybutyrate (PHB) are Group of the interesting biopolymers which have several medical applications such as drug delivery, suture, scaffold and heart valves. PHAs are biological macromolecules, thermoplastics, biodegradable and biocompatible. In this study, new bacterial isolates from Egypt were screened for their ability to produce PHB using Nile red dye. Out of 44 isolates, 19 bacterial isolates were selected according to strong of their fluorescence on mineral salt medium (MSM) agar plates supplemented with Nile red. The most potent strain was identified using biochemical tests as Bacillus sp. N-2. Production of PHB was carried out in limitation of nitrogen source using a minimal salt medium (MSM) supplemented with an excess of glucose as sole carbon source. PHB was accumulated in relation to cell dry weight about 20% (PHB/CDW). The obtained biopolymer was purified and analyzed using NMR, FT-IR, TGA and DSC thus; it was highly pure and identified as PHB. Optimization of PHB production from cheap sources appears to be a realistic goal in the future for reducing the costs and obtaining high yield.
Keywords: Biopolymer, PHB, Bacillus sp., Nile red dye, 1H NMR.